Microfibrillar-associated protein 2 is a prognostic marker that correlates with the immune microenvironment in glioma - Xu, Wanzhen; Geng, Ren; Zhao, Yao; Ma, Xiaoshan; Bai, Yang; Jiang, Yining; Zhao, Liyan; Li, Yunqian (Frontiers in Genetics, 2022)
Aims: microfibrillar-associated protein 2 (MFAP2), a component of the extracellular matrix, plays key roles in regulating growth factor signal transduction and various malignant tumors. However, the clinicopathological features of microfibrillar-associated protein 2 in gliomas have not been elucidated to date. Methods: TCGA and CGGA databases were used to study the expression of microfibrillar-associated protein 2 in glioma and its relationship with clinicopathological features of patients with glioma. Western blotting was performed to detect the expression of microfibrillar-associated protein 2 protein in tissue samples from glioma patients. Gene set enrichment analysis (GSEA) was applied to detect biological processes and signal pathways related to microfibrillar-associated protein 2. Single-sample gene set enrichment analysis, TIMER 2.0, and TISIDB databases were used to evaluate the role of microfibrillar-associated protein 2 in tumor immune characteristics. The prognostic role of microfibrillar-associated protein 2 in glioma was analyzed using the Kaplan-Meier method and Cox regression. Survival data were used to establish a nomogram prediction model. Results: microfibrillar-associated protein 2 expression was significantly elevated in gliomas. receiver operating characteristic analysis revealed good discrimination of microfibrillar-associated protein 2 between glioma and normal tissues. High expression of microfibrillar-associated protein 2 was associated with malignant phenotypes, such as histological type. Based on gene set enrichment analysis, we identified pathways associated with high microfibrillar-associated protein 2 expression. High microfibrillar-associated protein 2 expression was related to the infiltration of tumor immune cells, including Th2 cells and macrophages, and correlated with key markers of T-cell exhaustion. Based on the TISIDB database, microfibrillar-associated protein 2 was observed to be associated with chemokines, chemokine receptors, and multiple immunoinhibitors in glioma. Kaplan–Meier survival analyses revealed that high microfibrillar-associated protein 2 expression predicted poor overall survival, DSS, and PFS in patients with glioma. By combining microfibrillar-associated protein 2 and other prognostic factors, a nomogram prognostic prediction model was constructed, which demonstrated an ideal prediction effect. Conclusion: microfibrillar-associated protein 2 is a potential prognostic marker that plays a key role in glioma development given its association with malignant phenotypes, cancer-related pathways and tumor immunity.